(untitled) (Global Journal of Human-Social Science, 2021)
Development of new ideas and proposals related to administration and communication activities makes us turn to the past to find the points of departure in the history of development of this area of knowledge. This publication looks at a period starting from the Middle Ages to the beginning of the Age of the Enlightenment called the Renaissance. This was a period of rethinking the administration and communication ideas of the Antiquity based on Plato’s and Aristotle’s ideas. In this sense, two opposing trends were formed: from toughening and absolutizing standards in relations of power to, on the contrary, granting to the population more rights and opportunities for the freedom of speech and self-expression. The most prominent expressions of the following thinkers are presented: Francesco Petrarch, Leonardo Bruni, Niccolo Machiavelli, Hugo Grotius, Thomas Hobbes,